Implementation of Canva in Asmaul Husna Materials for Indonesian Migrant Workers’ Children at ICC Muar, Malaysia - Salsabila Aufa Khairunnisa; Sigit Dwi Laksana; Devid Dwi Erwahyudin; Navin Ruditiyawan Bin Mohd Mohan (UIN Sultan Aji Muhammad Idris Samarinda, 2026)
Abstract Access to quality education is a fundamental right and an important pillar in shaping an individual’s personality, including for Indonesian migrant workers’ children in Malaysia, who face limitations in obtaining educational services. This situation requires a more flexible, engaging, and easily absorbed learning approach for students. This study was designed to improve mastery of Asmaul Husna Material through the application of the Canva platform as a learning medium for Indonesian migrant workers’ children at ICC Muar, Malaysia. This Research adopted a Classroom Action Research (CAR) approach conducted in two cycles, covering the planning, action, observation, and reflection phases. Data were collected through direct observation, learning evaluation, and documentation techniques, which were then processed using the Miles, Huberman, and Saldana analysis framework. The study findings show progress in the learning process and outcomes after integrating Canva media. The student completion rate, which was initially only 22% on the pre-test, increased to 56% in cycle I, but this figure is still below the set success standard of 75%. After improvements were made, cycle II showed a significant jump with a completion rate of 85%. Learning with Canva has proven effective as an alternative instructional medium for Islamic Religious Education. It provides empirical evidence for the development of digital-based Islamic Religious Education in the context of non-formal education in migrant communities. Keywords: Asmaul Husna, Canva Based Learning, Islamic Education, Migrant Workers’ Children